Conductive corrosion-resistant carbon-carbon composite material as well as preparation method and application thereof

The carbon-carbon composite material prepared by high-temperature reaction under an inert atmosphere is filled with nanometal particles between graphite sheets, which solves the problems of single morphology and poor corrosion resistance of the existing carbon-carbon composite material, and improves the conductive and corrosion resistance of the material.

CN119840241AActive Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202311348673.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

The finished product form of existing carbon-carbon composite materials is relatively single, with only carbon main constituent elements, poor corrosion resistance, and lack of materials with high aspect ratio and fiber rod-like shape.

Method used

A carbon-carbon composite material prepared by reacting chopped carbon fibers, carbon sources and metal sources under an inert atmosphere at 1500-3500°C. This material consists of a single carbon fiber and a multi-layer graphite sheet surrounding its outer periphery, and nanometal particles are filled between any adjacent two layers of graphite sheets.

Benefits of technology

The conductive and corrosion resistance of carbon-carbon composite materials has been significantly improved, and the materials have excellent conductive and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119840241A_ABST
    Figure CN119840241A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, and discloses a conductive corrosion-resistant carbon-carbon composite material as well as a preparation method and application thereof. The carbon-carbon composite material comprises a single carbon fiber and multiple layers of graphite flakes surrounding the periphery of the single carbon fiber, nano metal particles are filled between any two adjacent layers of graphite flakes, and the nano metal particles contain a copper element, an iron element, an aluminum element and optional IVB group metal elements. The carbon-carbon composite material disclosed by the invention is composed of layered graphite flake clusters with concentric circle structures on the microscopic scale, the interior of the carbon-carbon composite material contains nano metal particles besides carbon, and metal elements are uniformly distributed in the graphite flake clusters with specific structures under the atomic scale; the carbon-carbon composite material with the characteristics has excellent conductivity and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a conductive and corrosion-resistant carbon-carbon composite material and a preparation method and application thereof. Background Art

[0002] Carbon fiber has comprehensive properties such as high tensile strength, high tensile modulus, low density, high temperature resistance, ablation resistance, corrosion resistance, high electrical and thermal conductivity, low thermal expansion, self-lubrication and good biocompatibility. Carbon fiber is widely used in aerospace, automotive industry, building energy and sports equipment. He Fu wrote in the fifth chapter of Carbon Fiber and Graphite Fiber (first edition in September 2010): Graphite fiber generally refers to carbon fiber with a carbon content of more than 99%. Carbon fiber can be obtained by high-temperature graphitization at 2200-3000℃. Graphite fiber not only has a high carbon content, but also has a high tensile modulus. Graphite fiber has excellent properties such as low thermal expansion coefficient, good thermal stability and dimensional stability. Therefore, it is used to manufacture rigid, thin and dimensionally stable composite materials and is widely used in the field of aerospace based on spacecraft. For example, the horn antenna of artificial satellites is made of high-model carbon fiber composite materials to ensure dimensional stability in the space environment with alternating temperature.

[0003] Carbon-carbon (C / C) composite material refers to a multiphase structural material with carbon fiber or its fabric as the reinforcing phase, pyrolytic carbon infiltrated by chemical vapor phase or liquid phase impregnation-carbonized resin carbon and asphalt carbon as the matrix (domestic patent: CN112125690A). It has extremely high specific strength and specific modulus. It can be used above 2000℃ in an inert atmosphere without reducing the mechanical properties. It has unparalleled characteristics of any other material. C / C composite materials are non-melting and non-combustible, and are evenly ablated. They are widely used in the outer wall materials of space shuttles, missile nose cones, and engine nozzles. C / C composite materials are excellent thermal conductive materials with small thermal expansion coefficients, friction resistance and wear resistance, and are widely used in aircraft brake devices. C / C composite materials are prepared by preforms made of carbon fiber filaments, or short-cut carbon fiber composite matrix carbon as embryos, which are densified by liquid phase impregnation and carbonization or chemical vapor deposition and chemical vapor infiltration.

[0004] The manufacture of carbon-carbon composites is an integration of high-temperature technology and high-temperature equipment. The key technology of its continuous graphitization preparation is to inhibit and regulate the high-temperature oxidation and high-temperature biochemistry (evaporation) of graphite heating elements and running fibers. Carbon-carbon composites have different forms of carbon materials in macroscopic terms because of different forms of stacking / arrangement in the three-dimensional space. These various forms of carbon materials are composed of microcrystals of different sizes and diverse orientations and stacking states. The nanocarbon fibers grown by catalytic vapor phase have different shapes. Different catalysts and raw materials produce tubular, herringbone and flat nanocarbon fibers with different structures.

[0005] CN111807853A discloses a preparation process and application of carbon-carbon composite parts, which uses carbon fiber, vapor deposition carbon and impregnation carbon composite, can maintain good mechanical, thermal and friction and wear properties at high temperature, reduce costs by 50%, and can be mass-produced. CN112125690A uses flake graphite and UV silica gel to prepare a mixed colloid, fills it in the middle of the mixed layer of carbon fiber and glass fiber to prepare an intermediate, and prepares a carbon-carbon composite material by hot pressing, curing and drying. The composite material has the advantages of high tensile strength and high elasticity. CN112679950A discloses a preparation method of a flexible carbon-carbon composite material, after covering the surface of the carbon fiber cloth with a thermosetting resin film, hot pressing and curing are carried out, and the composite material is obtained after carbonization in an inert atmosphere. The method has the advantages of short processing time, simple process, no need for high-pressure equipment, and high production efficiency, and can realize industrial production. CN113175565A discloses a thin-walled high-strength carbon-carbon composite pipe and a preparation method thereof, the pipe comprises a pipe body formed by laminating carbon cloth, a binder, and a CVD layer, and a dense layer located on the inner surface of the pipe body, the pipe has the advantages of reducing the wall thickness while maintaining the strength. CN113636854A discloses a carbon-carbon composite material with deposited carbon nanotubes, wherein chopped carbon fibers are embedded in a carbon matrix and carbon fibers, and carbon nanotubes are deposited between the two, which has the advantages of significantly improving the mechanical properties and anti-oxidation properties of the carbon-carbon composite material. CN113636855A discloses an internal anti-oxidation carbon-carbon composite material, comprising a carbon matrix, a carbon fiber reinforcement distributed in the carbon matrix, silicon carbide, zirconium oxide, and aluminum oxide, which has the advantages of improving the ablation resistance and service life of the composite material. CN113683437A discloses a carbon-carbon composite material containing refractory metal, including a carbon matrix, a carbon fiber reinforcement distributed in the carbon matrix, a metal zirconium-fullerene composite nanopowder, and silicon-rich silicon carbide, which has the advantages of improving the ablation resistance, service life and oxidation resistance of the composite material. CN115180969A discloses a high thermal conductivity carbon-carbon composite material and a preparation method thereof, which produces graphene / AIN reinforcement on the surface and inside of a carbon fiber needle-punched preform by electrophoresis, impregnates in benzoxazine resin, and after heat curing and carbonization at normal pressure, has the advantages of excellent mechanical properties and good thermal conductivity. CN115231941A relates to a carbon-carbon composite material for ultra-high temperature environment and a preparation method thereof, including a carbon matrix, a carbon fiber reinforcement, an ultra-high temperature ceramic and a carbon nanotube. The prepared carbon-carbon composite material has the advantages of excellent mechanical properties, high temperature ablation resistance and good thermal conductivity. CN213628313U discloses a carbon-carbon composite material plate, which has the advantages of light weight and high strength, high thermal conductivity and low expansion, good friction performance, good thermal shock resistance and high dimensional stability.

[0006] Existing public patent research shows that most of the current research work on C / C composite materials focuses on the improvement and optimization of their preparation process; focusing on solving the functional properties and application technical problems of C / C composite materials. However, the finished product form of C / C composite materials disclosed in the prior art is relatively simple, and the main component element is only carbon, the corrosion resistance is poor, and there are no reports on C / C composite materials with high aspect ratio and fiber rod morphology. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems in the prior art that the finished carbon-carbon composite material has a single form, the main component is only a single carbon element, and the corrosion resistance is poor. A conductive and corrosion-resistant carbon-carbon composite material and a preparation method and application thereof are provided. The carbon-carbon composite material is composed of layered graphite sheet clusters with a concentric circle structure on a microscopic scale. In addition to carbon, it also contains nano-metal particles, and non-carbon elements are uniformly distributed at the atomic scale. The carbon-carbon composite material with this feature has excellent conductive and corrosion-resistant properties.

[0008] In order to achieve the above-mentioned objectives, the present invention provides, on the one hand, a conductive and corrosion-resistant carbon-carbon composite material, which includes a single carbon fiber and multiple layers of graphite sheets surrounding the outer periphery of the single carbon fiber, and nanometal particles are filled between any two adjacent layers of graphite sheets, wherein the nanometal particles contain copper, iron, aluminum and optional IVB group metal elements.

[0009] Preferably, the carbon-carbon composite material contains 50-90 wt % of carbon, 1-15 wt % of copper, 0.5-10 wt % of iron, 0.1-5 wt % of aluminum and 0-1 wt % of Group IVB metal elements.

[0010] Preferably, the carbon-carbon composite material contains 60-70 wt % of carbon, 5-9 wt % of copper, 1-6 wt % of iron, 0.1-2.5 wt % of aluminum and 0.05-0.5 wt % of Group IVB metal elements.

[0011] Preferably, the Group IVB metal element is titanium and / or zirconium.

[0012] Preferably, the nano metal particles contain copper, iron, aluminum and titanium.

[0013] Preferably, the number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, more preferably 5-18 layers.

[0014] Preferably, the diameter of the single carbon fiber is 4-8 um, preferably 4.5-7.5 um; the length is 2-10 mm, preferably 3-9 mm.

[0015] Preferably, the thickness of the multi-layer graphite sheet gradually increases from the inside to the outside.

[0016] Preferably, the ratio of the total thickness of the multi-layer graphite sheet to the diameter of the single carbon fiber is 1-100:1.

[0017] Preferably, the carbon-carbon composite material is in a straight line or a curved shape.

[0018] Preferably, at least part of the surface of the carbon-carbon composite material is in a bamboo-node shape and / or a convex shape.

[0019] Preferably, the carbon-carbon composite material has a diameter of 0.02-1 mm, preferably 0.1-0.3 mm, and a length of 0.1-10 mm, preferably 1-5 mm.

[0020] Preferably, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.07-0.3:1.

[0021] Preferably, in the Raman spectrum of the carbon-carbon composite material, the ratio of the peak intensity of the 2D peak to the G peak is 0.2-1:1.

[0022] The second aspect of the present invention provides a method for preparing a conductive and corrosion-resistant carbon-carbon composite material, the method comprising: reacting chopped carbon fibers, a carbon source and a metal source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 20-1800 mL / min;

[0023] The metal source contains a copper source, an iron source, an aluminum source and an optional IVB group metal source.

[0024] Preferably, the weight ratio of the metal source, the carbon source and the chopped carbon fiber is 20-100:30-200:1, preferably 30-70:50-150:1;

[0025] The weight ratio of the copper source, the IVB group metal source, the iron source and the aluminum source is 10-100:0-50:5-10:1.

[0026] Preferably, the Group IVB metal source is a titanium source and / or a zirconium source.

[0027] Preferably, the metal source contains a copper source, an iron source, an aluminum source and a titanium source.

[0028] Preferably, the copper source is selected from one or more of CuSO4, CuO, CuCl2 and Cu(OH)2.

[0029] Preferably, the iron source is selected from one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, FeCl2, FeCl3 and FePO4.

[0030] Preferably, the aluminum source is selected from one or more of Al2O3, AlCl3, Al2(SO4)3, Al(OH)3 and AlPO4.

[0031] Preferably, the titanium source is selected from one or more of TiF4, TiF3, TiCl4, TiSO4 and TiO2.

[0032] Preferably, the carbon source is carbonized resin and / or graphite.

[0033] Preferably, the graphite is amorphous graphite.

[0034] Preferably, the reaction temperature is 1500-2800° C.; the reaction time is 12-720 hours, preferably 24-120 hours; and the volume flow rate of the inert atmosphere is 50-500 mL / min, preferably 100-300 mL / min.

[0035] Preferably, the length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; the specification is 12-320K, preferably 12-48K; and the carbon content is 85-95% by weight.

[0036] A third aspect of the present invention provides a conductive and corrosion-resistant carbon-carbon composite material prepared by the method described above.

[0037] A fourth aspect of the present invention provides the conductive and corrosion-resistant carbon-carbon composite material described above or use of the conductive and corrosion-resistant carbon-carbon composite material described above as a conductive and corrosion-resistant material.

[0038] The carbon-carbon composite material described in the present invention is composed of layered graphite sheet clusters with a concentric circle structure on a microscopic scale. In addition to carbon, it also contains nano-metal particles, and the metal elements are evenly distributed in the graphite sheet clusters with a specific structure at the atomic scale; the carbon-carbon composite material with this feature has excellent electrical conductivity and corrosion resistance.

[0039] The method for preparing a conductive and corrosion-resistant carbon-carbon composite material of the present invention is simple to operate, and the carbon-carbon composite material with excellent conductive properties and corrosion resistance can be obtained by mixing chopped carbon fibers, a carbon source and a metal source and reacting them directly under specific conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the microscopic morphology of the carbon-carbon composite material of Example 1.

[0041] Figure 2-Figure 5 Element distribution (element energy spectrum) of Cu, Fe, Al and Ti inside the carbon-carbon composite material of Example 1 respectively.

[0042] Figure 6 This is a schematic diagram of the surface morphology structure of the carbon-carbon composite material in Example 1.

[0043] Figure 7 This is a schematic diagram of the cross-sectional morphology structure of the carbon-carbon composite material of Example 1.

[0044] Figure 8 This is a 3D Raman imaging diagram of the cross section of the carbon-carbon composite material of Example 1 (wherein the Z direction is the intensity ratio of the D peak and the G peak). DETAILED DESCRIPTION

[0045] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0046] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0047] The first aspect of the present invention provides a conductive and corrosion-resistant carbon-carbon composite material, which includes a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, and nano-metal particles are filled between any two adjacent layers of graphite sheets.

[0048] The carbon-carbon composite material provided by the present invention has a special microscopic morphology, in which the center of the carbon-carbon composite material is a single carbon fiber, and the periphery of the single carbon fiber is surrounded by a plurality of graphite sheets with a concentric circle structure. Based on this special morphology, nano-metal particles can be filled between any two adjacent layers of graphite sheets, so that the nano-metal particles are evenly distributed between any two layers of graphite sheets, ensuring that the nano-metal particles can be evenly distributed in the carbon-carbon composite material, thereby ensuring that the carbon-carbon composite material has excellent corrosion resistance, and at the same time, the presence of carbon and metal makes the carbon-carbon composite material have better conductivity.

[0049] Specifically, the nano metal particles contain copper, iron, aluminum and optional IVB group metal elements. Nano metal particles containing these specific elements are filled between any two adjacent graphite sheets. Combining these specific metal elements can improve the corrosion resistance of the carbon-carbon composite material through synergistic effect.

[0050] In the present invention, the Group IVB metal element is not particularly limited. Specifically, the Group IVB metal element may be titanium and / or zirconium.

[0051] In a preferred embodiment, in order to further improve the corrosion resistance of the carbon-carbon composite material, the IVB group metal element is titanium, that is, the nano metal particles contain copper, iron, aluminum and titanium at the same time.

[0052] In order to ensure that the carbon-carbon composite material has both excellent electrical conductivity and excellent corrosion resistance, the ratio of each element in the carbon-carbon composite material can be appropriately controlled.

[0053] In some embodiments, the carbon-carbon composite material contains 50-90 wt % of carbon, 1-15 wt % of copper, 0.5-10 wt % of iron, 0.1-5 wt % of aluminum and 0-1 wt % of Group IVB metal.

[0054] In a preferred embodiment, the carbon-carbon composite material preferably contains 60-70 wt% of carbon, 5-9 wt% of copper, 1-6 wt% of iron, 0.1-2.5 wt% of aluminum and 0.05-0.5 wt% of Group IVB metal elements.

[0055] In the present invention, the number of graphite sheets with a concentric structure surrounding the outer periphery of the single carbon fiber is relatively large, which can make the nano-metal particles more evenly distributed between the graphite sheets, thereby improving the corrosion resistance of the carbon-carbon composite material. If the number of graphite sheets with a concentric structure surrounding the outer periphery of the single carbon fiber is relatively small, the corrosion resistance of the carbon-carbon composite material is relatively poor. Preferably, the number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, and more preferably 5-18 layers.

[0056] In the present invention, the diameter of the single carbon fiber can be a conventional choice in the art. In some embodiments, the diameter of the single carbon fiber can be 4-8 um, preferably 4.5-7.5 um.

[0057] The length of the single carbon fiber is comparable to the length of the carbon-carbon composite material; in some preferred embodiments, the length of the single carbon fiber may be 2-10 mm, preferably 3-9 mm.

[0058] The microscopic morphology of the carbon-carbon composite material of the present invention is quite special. It can be seen from a scanning electron microscope that, preferably, the thickness of the multilayer graphite sheets gradually increases from the inside to the outside, which can improve the stability of the concentric circle structure of the carbon-carbon composite material.

[0059] The approximate ratio of the volume content of carbon fiber and graphite in the carbon-carbon composite material can be inferred from the ratio of the total thickness of the graphite sheet to the diameter of a single carbon fiber. In a preferred embodiment, the ratio of the total thickness of the multilayer graphite sheet to the diameter of the single carbon fiber can be 1-100:1. Limiting the ratio of the total thickness of the graphite sheet to the diameter of a single carbon fiber within this range can improve the dimensional stability of the concentric circle structure of the carbon-carbon composite material, maintain the uniform dispersion and firm bonding between the layered graphite sheet clusters, carbon fibers and nano-metal particles, and thus improve the corrosion resistance of the carbon-carbon composite material.

[0060] In the present invention, the appearance of the carbon-carbon composite material is not limited and can be in various forms. Specifically, the carbon-carbon composite material is linear or curved as a whole.

[0061] The carbon-carbon composite material provided by the present invention further contains carbon particles existing independently or in aggregated form, wherein the carbon particles can be observed on the surface of the carbon-carbon composite material. Preferably, the particle size of the carbon particles is 0.02-2.00 mm.

[0062] In the present invention, due to the presence of nano-metal particles, the diameter of the carbon-carbon composite material is not uniform. Specifically, at least part of the surface of the carbon-carbon composite material is in a bamboo-like shape and / or a convex shape.

[0063] In some embodiments, the carbon-carbon composite material may have a diameter of 0.02-1 mm, preferably 0.1-0.3 mm, and a length of 0.1-10 mm, preferably 1-5 mm.

[0064] In the present invention, specifically, through Raman spectrum characterization, the peak intensity ratio of the D peak to the G peak of the carbon-carbon composite material can be 0.07-0.3: 1. When the peak intensity ratio of the D peak to the G peak is within this range, the smaller the carbon atom lattice defect is, the higher the conductivity of the carbon-carbon composite material is.

[0065] In the present invention, specifically, in the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the 2D peak to the G peak can be 0.2-1:1. When the peak intensity ratio of the 2D peak to the G peak is within this range, the carbon atoms have few lattice defects, the layered graphite sheet clusters have a complete and regular graphite structure, and the formed carbon-carbon composite material has good electrical conductivity.

[0066] Furthermore, the carbon-carbon composite material of the present invention is grey or black.

[0067] The carbon-carbon composite material of the present invention also contains a small amount of other metal elements, including zinc, manganese, silver, barium, lithium, magnesium, lead and strontium, and the content of each metal element is less than 0.001% by weight.

[0068] The carbon-carbon composite material of the present invention contains not only the aforementioned elements, but also elements such as oxygen, nitrogen, and sulfur. The metal elements in the carbon-carbon composite material exist in the form of compounds.

[0069] The second aspect of the present invention provides a method for preparing a conductive and corrosion-resistant carbon-carbon composite material, the method comprising: reacting chopped carbon fibers, a carbon source and a metal source at 1500-3500°C in the presence of an inert atmosphere, the volume flow rate of the inert atmosphere being 20-1800 mL / min; wherein the metal source contains a copper source, an iron source, an aluminum source and an optional IVB group metal source.

[0070] The method of the present invention is simple and easy to operate, and only requires that the chopped carbon fibers, a carbon source and a specific non-carbon element source be mixed and contacted and reacted under specific conditions.

[0071] In the method described in the present invention, if the reaction temperature is too low, graphite sheets with a concentric circle structure cannot be formed outside a single carbon fiber, resulting in the inability of nano-metal particles to adhere in large quantities and evenly to the surface of the graphite sheets, thereby resulting in poor corrosion resistance of the obtained material; if the reaction temperature is too high, the growth rate of the graphite sheets on the surface of the carbon fiber is much faster than the speed at which the nano-metal particles adhere to the graphite sheet layer, resulting in uneven distribution of the nano-metal particles on the graphite sheets, which also results in poor corrosion resistance of the obtained material.

[0072] In some embodiments, the reaction temperature may be 1500° C., 1800° C., 2000° C., 2200° C., 2500° C., 2800° C., 3000° C., 3200° C. or 3500° C. In a preferred embodiment, the reaction temperature is 1500-2800° C.

[0073] In some embodiments, the reaction time can be 12-720 hours. In a preferred embodiment, the reaction time is 24-120 hours, for example, 24 hours, 48 ​​hours, 72 hours, 80 hours, 100 hours or 120 hours.

[0074] In order to ensure that the chopped carbon fibers, carbon source and metal source can be used to prepare the carbon-carbon composite material of the above structure, the reaction needs to be carried out under inert atmosphere conditions. Specifically, the inert atmosphere is nitrogen and / or inert gas; the purity of nitrogen and inert gas is greater than 99.9% by volume, and the oxygen content in the inert atmosphere is less than 50ppm.

[0075] If there is no inert atmosphere for protection during the reaction, it is impossible to obtain a carbon-carbon composite material including a single carbon fiber and a multilayer graphite sheet surrounding the single carbon fiber, with nano-metal particles filled between any two adjacent graphite sheets. In addition, if the volume flow rate of the inert atmosphere is too large, it is impossible to maintain a microenvironment for the stable growth of the graphite sheet, and the nano-metal particles are even less likely to adhere to the surface of the graphite sheet.

[0076] In some embodiments, the volume flow rate of the inert atmosphere is 20-1800 mL / min. In a preferred embodiment, the volume flow rate of the inert atmosphere is 50-500 mL / min, more preferably 100-300 mL / min.

[0077] In the present invention, in order to obtain a carbon-carbon composite material with an appropriate ratio of carbon element to metal element content, a large number of graphite sheets surrounding the diameter of a single carbon fiber, and excellent electrical conductivity and corrosion resistance, the weight ratio of the chopped carbon fiber, the carbon source and the metal source can be appropriately controlled.

[0078] In some embodiments, the weight ratio of the metal source, the carbon source and the chopped carbon fiber is 20-100:30-200:1, preferably 30-70:50-150:1;

[0079] The weight ratio of the copper source, the iron source, the aluminum source and the Group IVB metal source is 10-100:5-10:1:0-50.

[0080] In the present invention, the metal source is used to generate nano-metal particles and fill them between graphite sheets. The IVB group metal source can be a conventional choice in the art; specifically, the IVB group metal source is a titanium source and / or a zirconium source.

[0081] In a preferred embodiment, the Group IVB metal source is a titanium source, that is, the metal source contains a copper source, an iron source, an aluminum source and a titanium source at the same time.

[0082] In the present invention, the copper source can be a conventional choice in the art, and can be a copper salt, copper oxide or copper hydroxide. Specifically, the copper source can be selected from one or more of CuSO4, CuO, CuCl2 and Cu(OH)2.

[0083] In the present invention, the iron source can be a conventional choice in the art, and can be an iron salt, an iron oxide or an iron hydroxide. Specifically, the iron source can be selected from one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, FeCl2, FeCl3 and FePO4.

[0084] In the present invention, the aluminum source can be a conventional choice in the art, and can be an aluminum salt, an aluminum oxide or an aluminum hydroxide. Specifically, the aluminum source can be selected from one or more of Al2O3, AlCl3, Al2(SO4)3, Al(OH)3 and AlPO4.

[0085] In the present invention, the titanium source can be a conventional choice in the art, and can be a titanium salt, titanium oxide or titanium hydroxide. Specifically, the titanium source can be selected from one or more of TiF4, TiF3, TiCl4, TiSO4 and TiO2.

[0086] In the method of the present invention, the role of the carbon source is to form a graphite sheet on the periphery of a single carbon fiber. The carbon source can be a conventional choice in the art, specifically, the carbon source can be a carbonized resin and / or graphite. Preferably, the carbonized resin is a resin carbide with a rich pore structure after high-temperature carbonization. Preferably, the graphite is amorphous graphite.

[0087] In the present invention, the reaction can be carried out in a conventional high-temperature furnace. Specifically, isostatic graphite or highly oriented graphite is used as a heating element in the high-temperature furnace. Preferably, the high-temperature furnace is connected to the tail gas recovery system through a pipeline, and a valve is provided on the pipeline connecting the high-temperature furnace and the tail gas recovery system. The inner diameter of the pipeline is between 5-20 mm. A filter is provided before the valve along the gas flow direction. The selection of the pipeline, the filter and the valve meets the temperature resistance requirements.

[0088] In the present invention, the single carbon fiber in the center of the carbon-carbon composite material is formed by chopped carbon fiber. In a specific embodiment, the length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; the specification is 12-320K, preferably 12-48K; and the carbon content is 85-95%.

[0089] A third aspect of the present invention provides a conductive, corrosion-resistant carbon-carbon composite material prepared by the method described above.

[0090] Preferably, the carbon-carbon composite material comprises a single carbon fiber and multiple layers of graphite sheets surrounding the single carbon fiber, and nano-metal particles are filled between any two adjacent layers of graphite sheets, wherein the nano-metal particles contain copper, iron, aluminum and optional IVB group metal elements.

[0091] A fourth aspect of the present invention provides the conductive and corrosion-resistant carbon-carbon composite material described above or use of the conductive and corrosion-resistant carbon-carbon composite material described above as a conductive and corrosion-resistant material.

[0092] The carbon-carbon composite material described in the present invention can be further processed as a raw material. The processing methods include but are not limited to blending (extrusion or granulation), strip making, grinding (crushing), and roasting. The types and contents of the constituent elements of the material products manufactured by the above-mentioned processing methods, as long as they fall within the scope of the claims and description of the present invention, belong to the protection scope of the present invention. It is further clarified that as long as the types and contents of the elements contained are within the specified scope of the present invention, whether it is a raw material or a finished product, and the shape of the material is not limited to a fiber shape; and it is not limited to the processing process of the material, it is within the protection scope of the present invention.

[0093] The present invention will be described in detail below by way of examples, but the protection scope of the present invention is not limited thereto. In the following examples, unless otherwise specified, all reagents used are commercially available.

[0094] In the following examples and comparative examples, the carbonized resin powder is YKD-508 hemoperfusion carbonized resin (carbon skeleton spherical porous adsorption resin) produced by Henan Yinkai New Materials Co., Ltd.

[0095] The test method adopted by the present invention comprises:

[0096] 1. The surface and cross-sectional morphology of the carbon-carbon composite materials prepared in the examples and comparative examples were observed using a ZEISS Merlin field emission scanning electron microscope, wherein the test conditions included: an acceleration voltage of 20 to 30 kV, and an electron beam current of 10 pA to 40 / 100 / 300 nA.

[0097] 2. The element types, distribution states and particle sizes of the carbon-carbon composite materials prepared in the examples and comparative examples were analyzed using an X-ray spectrometer configured with a field emission scanning electron microscope from German ZEISS Merlin. The surface scanning mode test conditions included: an acceleration voltage of 20 to 30 kV, an effective working area of ​​the probe of 150 mm 2 , element range Be~U, detection limit ≈0.1wt.%.

[0098] 3. Raman imaging analysis of the cross section of carbon-carbon composite materials: A laser micro-Raman spectrometer (micro-Raman spectroscopy analysis, RENISHAW, inVia Raman microscope, UK, 532nm line, helium-neon laser radiation model: QONTOR) is used to observe the cross-sectional morphology of the carbon-carbon composite materials prepared in the embodiments and comparative examples, and Raman imaging analysis of the cross-sectional morphology is performed, which can achieve high-sensitivity spectral analysis under high-resolution conditions. The specific method includes: directly breaking the carbon-carbon composite material, observing the morphology after the cross section appears, using Live TrackTM technology to focus in real time, and collecting each point in the test process in a focused state. The coordinates of each point in the Z-axis direction will be recorded to form a height imaging map of the surface, and the Raman imaging results can be superimposed on the height map. The in-situ Raman imaging area: 70um*70um, step length 1um, the recording range of the Raman spectrum is 400-3100cm -1 The integration time of each spectrum is 100s. The cross-sectional morphology of the fibrous composite material was observed under a 20x objective lens, and the Raman spectrum was collected somewhere in the 1um*1um area. The spectrum has a wavelength of 1350cm -1 Nearby D peak, 1582cm -1 The nearby G peak, and 2699cm -1 The 2D peak nearby; also use Raman imaging to see the intensity distribution of the D peak at different points.

[0099] 4. The types and contents of non-carbon elements in the carbon-carbon composite materials prepared in the examples and comparative examples were tested using an inductively coupled plasma emission spectrometer.

[0100] The main instruments and reagents are as follows:

[0101] (1) Varian 725-ES inductively coupled plasma optical emission spectrometer;

[0102] (2) Haoyue HMF1600-40 box-type furnace;

[0103] (3) Labtech Digiblock ST36 electric heating digestion instrument;

[0104] (4) Multi-element standard solution: 1000ug / mL (Steel Research Institute Nano-Test Technology Co., Ltd.); praseodymium standard stock solution: 1000ug / mL (National Nonferrous Metals and Electronic Materials Analysis and Testing Center); vanadium standard stock solution: 1000ug / mL (National Nonferrous Metals and Electronic Materials Analysis and Testing Center); The ultrapure water used in the experiment was prepared by the Genie Purist intelligent ultrapure water system of Lefeng (resistivity = 18.2MΩcm, 25°C); hydrogen peroxide (30wt%), hydrochloric acid, nitric acid, and hydrofluoric acid were all of premium grade purity; sulfuric acid was of process ultrapure purity (Sinopharm Chemical Reagent Co., Ltd.); liquid argon (Chart Cryogenic Engineering Systems (Changzhou) Co., Ltd.).

[0105] The working conditions of the instrument are as follows:

[0106] Instrument operating parameters: high frequency power: 1100W; plasma gas flow rate: 15L min -1 ; Auxiliary gas flow: 1.5Lmin -1 ; Atomizing gas flow rate: 0.75L min -1 ; Injection pump speed: 15rpm; Observation height: 10mm.

[0107] The experimental method is as follows:

[0108] (1) Accurately weigh 0.1g of sample into a clean quartz crucible, place it in a box furnace, and gradually heat it to 930℃ for ash treatment to obtain ash. The weight percentage of the sample reduced during the calcination process is the carbon content of the fibrous carbon-carbon composite material in this patent;

[0109] (2) Use a small amount of ultrapure water to transfer all the ash into a PFA test tube, add aqua regia, hydrogen peroxide, sulfuric acid and hydrofluoric acid in sequence, cover and place in an electric heating digestion instrument to heat until the sample is completely digested;

[0110] (3) Remove the test tube and cool it to room temperature. Use ultrapure water to transfer it to a 50 mL volumetric flask and make up to volume for testing.

[0111] (4) Prepare a mixed standard solution of the elements, draw a test spectrum, use an inductively coupled plasma spectrometer to detect the solution to be tested, and calculate the content of each element according to the drawn test spectrum.

[0112] Example 1

[0113] The method for preparing the carbon-carbon composite material comprises:

[0114] In the presence of nitrogen, short carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0115] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 30:80:1, and the weight ratio of the metal sources CuO, Fe2O3, Al2O3 and TiF4 is 20:8:1:15.

[0116] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.

[0117] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0118] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0119] (1) Figure 7 As shown, the center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets with a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 9:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.1mm, and the length is 3mm;

[0120] (2) The carbon-carbon composite material is gray. There are carbon particles on the surface of the carbon-carbon composite material. The particle size of the carbon particles is 0.05 mm. The carbon-carbon composite material is curved in the axial direction, and some surfaces are bamboo-like and convex (such as Figure 1 , Figure 6 As shown); in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.158:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.477:1;

[0121] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 60 weight %; copper content of 8.5 weight %; iron content of 5.5 weight %; aluminum content of 2.5 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0122] The characteristics of step (1) and step (2) were obtained by using a ZEISS Merlin field emission scanning electron microscope and an X-ray energy spectrometer configured with a field emission scanning electron microscope of ZEISS Merlin, Germany;

[0123] from Figure 2-Figure 5 It can be seen from the element spectrum that the copper ( Figure 2 ),iron( Figure 3 ),aluminum( Figure 4 ),titanium( Figure 5 ) are evenly distributed and are nanoparticles.

[0124] Example 2

[0125] The method for preparing the carbon-carbon composite material comprises:

[0126] In the presence of nitrogen, short-cut carbon fibers (24K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite and metal sources were reacted in a high-temperature furnace for 150 hours.

[0127] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 90:190:1, and the weight ratio of the metal sources CuCl2, Fe3O4, Al(OH)3 and TiO2 is 18:5:1:12.

[0128] The high-temperature furnace uses highly oriented graphite as the heating element, the center temperature is 3000°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 350mL / min.

[0129] A valve is provided on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 5mm. A filter is provided before the valve along the gas flow direction.

[0130] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0131] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 8 layers of graphite sheets in a concentric circle structure, the thickness of the 8 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 8 layers of graphite sheets to the diameter of the single carbon fiber is 48:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.5mm, and the length is 6mm;

[0132] (2) The carbon-carbon composite material is black, and the surface of each graphite sheet is distributed with carbon particles in the form of aggregation, and the particle size of the carbon particles is 1.5 mm; the carbon-carbon composite material is linear in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.160:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.483:1;

[0133] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 71 weight %; copper content of 9.5 weight %; iron content of 6.8 weight %; aluminum content of 3.3 weight %; titanium content of 0.7 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0134] Example 3

[0135] The method for preparing the carbon-carbon composite material comprises:

[0136] In the presence of nitrogen, short-cut carbon fibers (specification 50K, length 9 mm, carbon content 90 wt%), amorphous graphite and metal source were reacted in a high temperature furnace for 80 hours.

[0137] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 60:100:1, and the weight ratio of the metal sources CuO, Fe2O3, Al2O3 and TiF4 is 35:10:1:30.

[0138] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 400mL / min.

[0139] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 15mm. A filter is installed before the valve along the gas flow direction.

[0140] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0141] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 9mm; the outer periphery of the single carbon fiber is surrounded by 6 layers of graphite sheets in a concentric circle structure, the thickness of the 6 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 6 layers of graphite sheets to the diameter of the single carbon fiber is 30:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.3mm and the length is 9mm;

[0142] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.09 mm; the carbon-carbon composite material is linear in the axial direction, and part of the surface is bamboo-like; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.180, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.549:1;

[0143] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 61 weight %; copper content of 8.9 weight %; iron content of 7.7 weight %; aluminum content of 4.1 weight %; titanium content of 0.3 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0144] Example 4

[0145] The method for preparing the carbon-carbon composite material comprises:

[0146] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite and metal sources were reacted in a high-temperature furnace for 150 hours.

[0147] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 40:120:1, and the weight ratio of the metal sources CuCl2, Fe3O4, Al(OH)3 and TiO2 is 15:5:1:10.

[0148] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 500mL / min.

[0149] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 20 mm. A filter is installed before the valve along the gas flow direction.

[0150] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0151] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 7um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 15 layers of graphite sheets in a concentric circle structure, the thickness of the 15 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 15 layers of graphite sheets to the diameter of the single carbon fiber is 65:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.7mm and the length is 6mm;

[0152] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 1.2 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.177:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.550:1;

[0153] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 67 weight %; copper content of 7.3 weight %; iron content of 4.2 weight %; aluminum content of 2.8 weight %; titanium content of 0.6 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0154] Example 5

[0155] The method for preparing the carbon-carbon composite material comprises:

[0156] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 9 mm in length, 95 wt% in carbon content), amorphous graphite and metal sources were reacted in a high-temperature furnace for 36 hours.

[0157] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 20:50:1, and the weight ratio of the metal sources CuCl2, Fe3O4, Al(OH)3 and TiO2 is 10:5:1:10.

[0158] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 50mL / min.

[0159] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 20 mm. A filter is installed before the valve along the gas flow direction.

[0160] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0161] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 7um, and the length is 9mm; the outer periphery of the single carbon fiber is surrounded by 16 layers of graphite sheets in a concentric circle structure, the thickness of the 16 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 16 layers of graphite sheets to the diameter of the single carbon fiber is 58:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.8mm and the length is 9mm;

[0162] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 1.3 mm; the carbon-carbon composite material is curved in the axial direction, and part of the surface is bamboo-like and convex; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.186:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.555:1;

[0163] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 69 weight %; copper content of 7.5 weight %; iron content of 4.9 weight %; aluminum content of 2.5 weight %; titanium content of 0.8 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0164] Example 6

[0165] The method for preparing the carbon-carbon composite material comprises:

[0166] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite and metal sources were reacted in a high-temperature furnace for 120 hours.

[0167] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 30:80:1, and the weight ratio of the metal sources CuCl2, Fe3O4, Al(OH)3 and TiO2 is 25:5:1:20.

[0168] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 100mL / min.

[0169] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0170] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0171] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 18 layers of graphite sheets in a concentric circle structure, the thickness of the 18 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 18 layers of graphite sheets to the diameter of the single carbon fiber is 100:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 1.0mm, and the length is 6mm;

[0172] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 1.5 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.183:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.551:1;

[0173] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 66 weight %; copper content of 7.2 weight %; iron content of 4.4 weight %; aluminum content of 2.2 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0174] Example 7

[0175] The method for preparing the carbon-carbon composite material comprises:

[0176] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite and metal sources were reacted in a high-temperature furnace for 144 hours.

[0177] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 40:100:1, and the weight ratio of the metal sources CuCl2, Fe3O4, Al(OH)3 and TiO2 is 15:5:1:10.

[0178] The high temperature furnace uses isostatic graphite as the heating element, the center temperature is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 200mL / min.

[0179] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0180] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0181] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 12 layers of graphite sheets in a concentric circle structure, the thickness of the 12 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 12 layers of graphite sheets to the diameter of the single carbon fiber is 41:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.4mm, and the length is 5mm;

[0182] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 0.6 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.184:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.552:1;

[0183] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 65 weight %; copper content of 7.1 weight %; iron content of 4.1 weight %; aluminum content of 2.6 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0184] Example 8

[0185] The method for preparing the carbon-carbon composite material comprises:

[0186] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite and metal sources were reacted in a high-temperature furnace for 72 hours.

[0187] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 70:120:1, and the weight ratio of the metal sources CuCl2, Fe3O4, Al(OH)3 and TiO2 is 40:12:1:20.

[0188] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 300mL / min.

[0189] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0190] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0191] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 13 layers of graphite sheets in a concentric circle structure, the thickness of the 13 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 13 layers of graphite sheets to the diameter of the single carbon fiber is 49:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.5mm, and the length is 6mm;

[0192] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, and the particle size of the carbon particles is 1 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.179:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.549:1;

[0193] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 65 weight %; copper content of 7.2 weight %; iron content of 4.4 weight %; aluminum content of 2.3 weight %; titanium content of 0.2 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0194] Example 9

[0195] The method for preparing the carbon-carbon composite material comprises:

[0196] In the presence of nitrogen, short-cut carbon fibers (12K in specification, 6 mm in length, 95 wt% in carbon content), amorphous graphite and metal sources were reacted in a high-temperature furnace for 48 hours.

[0197] The weight ratio of the metal source, amorphous graphite and chopped carbon fiber is 80:110:1, and the weight ratio of the metal source CuCl2, Fe3O4, Al(OH)3 and TiO2 is 10:10:1:10.

[0198] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2800°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 20ppm, and the gas flow rate is 500mL / min.

[0199] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0200] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0201] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 6mm; the outer periphery of the single carbon fiber is surrounded by 16 layers of graphite sheets in a concentric circle structure, the thickness of the 16 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 16 layers of graphite sheets to the diameter of the single carbon fiber is 90:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.9mm, and the length is 6mm;

[0202] (2) The carbon-carbon composite material is black, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 1.2 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.179:1, and the peak intensity ratio of the 2D peak to the G peak is 0.553:1;

[0203] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 68 weight %; copper content of 6.8 weight %; iron content of 4.9 weight %; aluminum content of 2.8 weight %; titanium content of 1.2 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0204] Example 10

[0205] The method of Example 1 is followed, except that no titanium source TiF4 is added.

[0206] The method for preparing the carbon-carbon composite material comprises:

[0207] In the presence of nitrogen, short carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0208] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 30:80:1, and the weight ratio of the metal source CuO, Fe2O3 and Al2O3 is 20:8:1.

[0209] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.

[0210] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0211] The carbon-carbon composite material prepared in this embodiment has the following characteristics:

[0212] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets in a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 8:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.09mm, and the length is 3mm;

[0213] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material with a particle size of 0.05 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.156:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.475:1;

[0214] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 60 weight %; copper content of 8.5 weight %; iron content of 5.5 weight %; aluminum content of 3 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0215] Comparative Example 1

[0216] The method of Example 1 is followed, except that no chopped carbon fibers are added into the high-temperature furnace.

[0217] In this comparative example, due to the lack of chopped carbon fibers, the metal particles cannot form growth attachment points, and the carbon vapor can only grow into blocky carbon-containing materials with extremely high carbon content on the surface of the inner wall of the high-temperature furnace, and the carbon-carbon composite material described in the present invention cannot be obtained.

[0218] The material obtained in this comparative example is a bulk product formed by a carbon source, and the material contains 99.9 wt % of carbon, and does not contain Cu, Fe, Al and Ti.

[0219] Comparative Example 2

[0220] The method of Example 1 was followed, except that the reaction process was not protected by an inert atmosphere.

[0221] Due to the lack of inert atmosphere protection, the carbonized resin powder is oxidized into carbon dioxide, and the short-cut carbon fibers with higher temperature resistance are broken into short-cut carbon fibers with uneven shapes and oxidized and etched surfaces. It is impossible to form a concentric circle structure with multiple layers of graphite sheets surrounding a single carbon fiber, and it is impossible to fill nano-metal particles. Therefore, the carbon-carbon composite material described in the present invention cannot be obtained.

[0222] The material obtained in this comparative example contained 99.9 wt % of carbon and contained no Cu, Fe, Al and Ti.

[0223] Comparative Example 3

[0224] The method of Example 1 is followed, except that no carbonized resin powder and metal source are added to the high-temperature furnace.

[0225] The material obtained in this comparative example is a product formed by chopped carbon fibers, and the material contains 99.9% by weight of carbon, and does not contain Cu, Fe, Al and Ti, and the carbon-carbon composite material of the present invention cannot be obtained.

[0226] Comparative Example 4

[0227] The method of Example 1 is followed, except that the center temperature is 1200°C.

[0228] In this comparative example, since the temperature is too low, the carbon in the carbonized resin powder cannot grow further on the surface of a single carbon fiber, and the metal particles cannot adhere to the surface of the carbon fiber or graphite sheet, and the carbon-carbon composite material of the present invention cannot be obtained.

[0229] The material prepared in this comparative example is a mixture formed by independent reactions of chopped carbon fibers, carbonized resin powder and metal source.

[0230] Comparative Example 5

[0231] The method of Example 1 was followed, except that the gas flow rate was 2000 mL / min.

[0232] In this comparative example, since the gas flow rate is too large, the microenvironment for the stable growth of graphite sheets cannot be maintained, and the metal particles cannot adhere to the surface of carbon fibers or graphite sheets, and the carbon-carbon composite material of the present invention cannot be obtained.

[0233] The material prepared in this comparative example is a mixture formed by independent reactions of chopped carbon fibers, carbonized resin powder and metal source.

[0234] Comparative Example 6

[0235] The method of Example 1 is followed, except that no metal sources CuO, Fe2O3, Al2O3 and TiF4 are added to the high temperature furnace.

[0236] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0237] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets with a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 10:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.1mm, and the length is 3mm;

[0238] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material with a particle size of 0.05 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.182:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.545:1;

[0239] (3) The main elements contained in the carbon-carbon composite material include: carbon content is 99.9% by weight; elements whose content is less than 0.001% by weight include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0240] Comparative Example 7

[0241] The method of Example 1 is followed, except that Fe2O3 is replaced by Co2O3.

[0242] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0243] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets in a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 9:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.1mm, and the length is 3mm;

[0244] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.05 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.158:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.477;

[0245] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 60 weight %; copper content of 8.5 weight %; cobalt content of 7.9 weight %; aluminum content of 3 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0246] Comparative Example 8

[0247] The method of Example 1 is followed, except that CuO is replaced by ZnO.

[0248] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0249] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets in a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 9:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.1mm, and the length is 3mm;

[0250] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.05 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.158:1, and the peak intensity ratio of the 2D peak to the G peak is 0.477:1;

[0251] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 60 weight %; zinc content of 4.8 weight %; iron content of 5.5 weight %; aluminum content of 3 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: copper, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0252] Comparative Example 9

[0253] The method of Example 1 is followed, except that no aluminum source is added, that is, the metal sources are CuO, Fe2O3 and TiF4.

[0254] The method for preparing the carbon-carbon composite material comprises:

[0255] In the presence of nitrogen, short carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0256] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 30:80:1, and the weight ratio of the metal source CuO, Fe2O3 and TiF4 is 21:8:15.

[0257] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.

[0258] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0259] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0260] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets in a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 11:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.1mm, and the length is 3mm;

[0261] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.05 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.182:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.553:1;

[0262] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 60 weight %; copper content of 8.5 weight %; iron content of 5.5 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0263] Comparative Example 10

[0264] The method of Example 1 is followed, except that no iron source is added, that is, the metal sources are CuO, Al2O3 and TiF4.

[0265] The method for preparing the carbon-carbon composite material comprises:

[0266] In the presence of nitrogen, short carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0267] The weight ratio of chopped carbon fiber, carbonized resin powder and metal source is 30:80:1, and the weight ratio of CuO, Al2O3 and TiF4 as metal sources is 28:1:15.

[0268] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.

[0269] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0270] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0271] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets with a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 10:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.1mm, and the length is 3mm;

[0272] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material, with a particle size of 0.05 mm; the carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface; in the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.185:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.545:1;

[0273] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 60 weight %; copper content of 8.5 weight %; aluminum content of 3 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0274] Comparative Example 11

[0275] The method of Example 1 is followed, except that no copper source is added, that is, the metal sources are Fe2O3, Al2O3 and TiF4.

[0276] The method for preparing the carbon-carbon composite material comprises:

[0277] In the presence of nitrogen, short carbon fibers (12K in specification, 3 mm in length, 90% carbon content by weight), carbonized resin powder and metal source were reacted in a high temperature furnace for 48 hours.

[0278] The weight ratio of the metal source, carbonized resin powder and chopped carbon fiber is 30:80:1, and the weight ratio of the metal sources Fe2O3, Al2O3 and TiF4 is 28:1:15.

[0279] The high-temperature furnace uses isostatic graphite as the heating element, the center temperature is 2200°C, the purity of nitrogen is 99.99% by volume, the oxygen concentration is 40ppm, and the gas flow rate is 100mL / min.

[0280] A valve is installed on the pipeline connecting the high-temperature furnace and the exhaust gas recovery system. The valve is fully open. The inner diameter of the pipeline is 10mm. A filter is installed before the valve along the gas flow direction.

[0281] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0282] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by 10 layers of graphite sheets in a concentric circle structure, the thickness of the 10 layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the 10 layers of graphite sheets to the diameter of the single carbon fiber is 9:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.1mm, and the length is 3mm;

[0283] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material with a particle size of 0.05 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.180:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.549:1.

[0284] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 60 weight %; iron content of 5.5 weight %; aluminum content of 3 weight %; titanium content of 0.5 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0285] Comparative Example 12

[0286] The method of Example 1 was followed, except that the gas flow rate was 10 mL / min.

[0287] The carbon-carbon composite material prepared in this comparative example has the following characteristics:

[0288] (1) The center is a single carbon fiber, the diameter of the single carbon fiber is 5um, and the length is 3mm; the outer periphery of the single carbon fiber is surrounded by two layers of graphite sheets with a concentric circle structure, the thickness of the two layers of graphite sheets gradually increases from the inside to the outside, and the ratio of the total thickness of the two layers of graphite sheets to the diameter of the single carbon fiber is 1.1:1; nano-metal particles are filled between any two adjacent layers of graphite sheets; the diameter of the carbon-carbon composite material is 0.015mm, and the length is 3mm;

[0289] (2) The carbon-carbon composite material is gray, and there are carbon particles on the surface of the carbon-carbon composite material with a particle size of 0.01 mm. The carbon-carbon composite material is curved in the axial direction, and block-like protrusions are distributed on part of the surface. In the Raman imaging spectrum of the carbon-carbon composite material, the average value of the peak intensity ratio of the D peak to the G peak is 0.177:1, and the average value of the peak intensity ratio of the 2D peak to the G peak is 0.530:1.

[0290] (3) The main elements contained in the carbon-carbon composite material include: carbon content of 95 weight %; copper content of 0.6 weight %; iron content of 0.1 weight %; aluminum content of 0.2 weight %; titanium content of 0.05 weight %. Elements with a content of less than 0.001 weight % include: zinc, manganese, silver, barium, lithium, magnesium, lead and strontium.

[0291] Test Case

[0292] The resistivity of the materials prepared in the examples and comparative examples was tested according to the national standard GB / T24525-2009 "Method for Determining Resistivity of Carbon Materials". The results are shown in Table 1, indicating that the resistivity is small and the conductivity is good.

[0293] The test method for the corrosion resistance of the materials prepared in the embodiments and comparative examples is as follows: the material is placed in a mixed solution of hydrofluoric acid and nitric acid with a concentration of 100 mass% (the weight ratio of hydrofluoric acid to nitric acid is 1:2) for detection. After corrosion for 300 hours, the corrosion rate (c%) of the material is calculated. The corrosion rate is the ratio of the mass difference of the material before and after corrosion to the mass of the material before corrosion. The results are shown in Table 1. The smaller the corrosion rate, the better the corrosion resistance.

[0294] Table 1

[0295]

[0296]

[0297] It can be seen from Table 1 that the resistivity and corrosion rate of the material in the embodiment are significantly lower than those in the comparative example. It can be seen that the carbon-carbon composite material prepared by the technical solution of the present invention has excellent electrical conductivity and corrosion resistance.

[0298] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A conductive and corrosion-resistant carbon-carbon composite material, characterized in that: The carbon-carbon composite material comprises a single carbon fiber and multiple layers of graphite sheets surrounding the outer periphery of the single carbon fiber, and nano-metal particles are filled between any two adjacent layers of graphite sheets. The nano metal particles contain copper, iron, aluminum and optional IVB group metal elements.

2. The carbon-carbon composite material according to claim 1, characterized in that: The carbon-carbon composite material contains 50-90 wt% of carbon, 1-15 wt% of copper, 0.5-10 wt% of iron, 0.1-5 wt% of aluminum and 0-1 wt% of Group IVB metal elements; Preferably, the carbon-carbon composite material contains 60-70 wt % of carbon, 5-9 wt % of copper, 1-6 wt % of iron, 0.1-2.5 wt % of aluminum and 0.05-0.5 wt % of Group IVB metal elements.

3. The carbon-carbon composite material according to claim 1 or 2, characterized in that: The IVB group metal element is titanium and / or zirconium.

4. The carbon-carbon composite material according to any one of claims 1 to 3, characterized in that: The nano metal particles contain copper, iron, aluminum and titanium elements.

5. The carbon-carbon composite material according to any one of claims 1 to 4, characterized in that: The number of graphite sheets surrounding the outer periphery of the single carbon fiber is 3-20 layers, more preferably 5-18 layers.

6. The carbon-carbon composite material according to any one of claims 1 to 5, characterized in that: The diameter of the single carbon fiber is 4-8 um, preferably 4.5-7.5 um; the length is 2-10 mm, preferably 3-9 mm.

7. The carbon-carbon composite material according to any one of claims 1 to 6, characterized in that: The thickness of the multilayer graphite sheet increases gradually from the inside to the outside; Preferably, the ratio of the total thickness of the multi-layer graphite sheet to the diameter of the single carbon fiber is 1-100:

1.

8. The carbon-carbon composite material according to any one of claims 1 to 7, characterized in that: The carbon-carbon composite material is in a straight line or a curved shape; Preferably, at least part of the surface of the carbon-carbon composite material is in a bamboo-like shape and / or a convex shape; Preferably, the carbon-carbon composite material has a diameter of 0.02-1 mm, preferably 0.1-0.3 mm, and a length of 0.1-10 mm, preferably 1-5 mm.

9. The carbon-carbon composite material according to any one of claims 1 to 8, characterized in that: In the Raman spectrum of the carbon-carbon composite material, the peak intensity ratio of the D peak to the G peak is 0.07-0.3:1; Preferably, in the Raman spectrum of the carbon-carbon composite material, the ratio of the peak intensity of the 2D peak to the G peak is 0.2-1:

1.

10. A method for preparing a conductive and corrosion-resistant carbon-carbon composite material, characterized in that: The method comprises: reacting chopped carbon fibers, a carbon source and a metal source at 1500-3500° C. in the presence of an inert atmosphere, wherein the volume flow rate of the inert atmosphere is 20-1800 mL / min; The metal source contains a copper source, an iron source, an aluminum source and an optional IVB group metal source.

11. The method according to claim 10, characterized in that The weight ratio of the metal source, the carbon source and the chopped carbon fiber is 20-100:30-200:1, preferably 30-70:50-150:1; The weight ratio of the copper source, the iron source, the aluminum source and the Group IVB metal source is 10-100:5-10:1:0-50.

12. The method according to claim 10 or 11, characterized in that: The Group IVB metal source is a titanium source and / or a zirconium source.

13. The method according to claims 10-12, characterized in that The metal source contains a copper source, an iron source, an aluminum source and a titanium source; Preferably, the copper source is selected from one or more of CuSO4, CuO, CuCl2 and Cu(OH)2; Preferably, the iron source is selected from one or more of FeO, Fe2O3, Fe3O4, Fe(OH)2, Fe(OH)3, FeCl2, FeCl3 and FePO4; Preferably, the aluminum source is selected from one or more of Al2O3, AlCl3, Al2(SO4)3, Al(OH)3 and AlPO4; Preferably, the titanium source is selected from one or more of TiF4, TiF3, TiCl4, TiSO4 and TiO2.

14. The method according to any one of claims 10 to 13, characterized in that: The carbon source is carbonized resin and / or graphite; Preferably, the graphite is amorphous graphite.

15. The method according to any one of claims 10 to 14, characterized in that: The reaction temperature is 1500-2800° C.; the reaction time is 12-720 hours, preferably 24-120 hours; the volume flow rate of the inert atmosphere is 50-500 mL / min, preferably 100-300 mL / min.

16. The method according to any one of claims 10 to 15, characterized in that: The length of the chopped carbon fiber is 0.1-10 mm, preferably 1-5 mm; the specification is 12-320K, preferably 12-48K; and the carbon content is 85-95% by weight.

17. The conductive and corrosion-resistant carbon-carbon composite material prepared by the method according to any one of claims 10 to 16.

18. Use of the conductive and corrosion-resistant carbon-carbon composite material according to any one of claims 1 to 9 or the conductive and corrosion-resistant carbon-carbon composite material according to claim 17 as a conductive and corrosion-resistant material.

Citation Information

Patent Citations

  • Carbon-carbon composite material as well as preparation process and application thereof

    CN111807853A

  • Manufacturing process of carbon-carbon composite material

    CN112125690A

  • Preparation method of flexible carbon-carbon composite material

    CN112679950A

  • Thin-wall high-strength carbon-carbon composite material pipeline and preparation method thereof

    CN113175565A

  • Carbon nano tube deposited carbon-carbon composite material

    CN113636854A